Co-ordination of base excision repair and genome stability. - Parsons, J; Dianov, G (2013)
Base excision repair (BER) is a major DNA repair pathway employed in mammalian cells that is required to maintain genome stability, thus preventing several human diseases, such as ageing, neurodegenerative diseases and cancer. This is achieved through the repair of damaged DNA bases, sites of base loss and single strand breaks of varying complexity that are continuously induced endogenously or via exogenous mutagens. Whilst the enzymes involved in BER are now well known and characterised, the role of the co-ordination of BER enzymatic activities in the cellular response to DNA damage and the mechanisms regulating this process are only now being revealed. Post-translational modifications of BER proteins, including ubiquitylation and phosphorylation, are increasingly being identified as key processes that regulate BER. In this review we will summarise recent evidence discovering novel mechanisms that are involved in maintaining genome stability by regulation of the key BER proteins in response to DNA damage.